Water in an Abbasid City: The Sources, Distribution, and Significance of Water at Samarra - Brown, Peter J. (Journal of Abbasid Studies, 2025)
This paper approaches the city of Samarra through one of its most fundamental attributes — the water supply. In seeking to understand how water was transported to, and distributed throughout, the vast metropolitan area, as well as the significance of the various pieces of hydraulic infrastructure required for this task, new light is shed on the occupation of the short-lived Abbasid caliphal capital, the priorities of its rulers, and the lives of its inhabitants.